2000
DOI: 10.1086/315593
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of Viral Gastroenteritis in Japan: Pediatric Cases and Outbreak Incidents

Abstract: Surveillance results from pediatric cases and outbreaks of viral gastroenteritis in Japan are presented. In winter, both small round structured virus (SRSV, or Norwalk-like viruses) and rotavirus were detected from infants with gastroenteritis; however, in recent years, the prevailing time of SRSV infection has preceded that of rotavirus infection. Most nonbacterial gastroenteritis outbreaks were related to SRSV infection, and >60% of the outbreaks were caused by contaminated food. In small-sized outbreaks, ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
79
0
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(89 citation statements)
references
References 0 publications
7
79
0
2
Order By: Relevance
“…Several studies show the occurrence of calicivirus, mainly NoV, during the colder months of the year (Xi et al 1990, Inouye et al 2000, Mounts et al 2000, while other show the circulation of these agents at different periods (Wright et al 1998, Greening et al 2001. The climate in the West Central region is sub-tropical and in Goiânia, temperatures are almost invariable throughout the year.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies show the occurrence of calicivirus, mainly NoV, during the colder months of the year (Xi et al 1990, Inouye et al 2000, Mounts et al 2000, while other show the circulation of these agents at different periods (Wright et al 1998, Greening et al 2001. The climate in the West Central region is sub-tropical and in Goiânia, temperatures are almost invariable throughout the year.…”
Section: Discussionmentioning
confidence: 99%
“…The prototype strain of human norovirus is the Norwalk virus (NV/Human/US/1968), which was first discovered in an outbreak of gastroenteritis in an elementary school in Norwalk, OH, in 1968 (15). Noroviruses are the leading cause of outbreaks of gastroenteritis in the world; they cause outbreaks in various settings, including hospitals, cruise ships, schools, and restaurants (2,9,12,15,23,24,29). In addition, noroviruses have been detected in environmental samples (e.g., treated and untreated sewage) as well as in contaminated foods such as oysters, shellfish, sandwiches, salads, raspberries, and even ice (7,18,19,26).…”
mentioning
confidence: 99%
“…Seroprevalence studies of NLV infections in pediatric cases of gastroenteritis suggested high exposure to NLVs among children (5,20). Since the development of the reverse transcription (RT)-PCR (2, 12) method for detection of NLVs, NLV infections among children have been reported, and NLVs have been identified as a causative agent of gastroenteritis (3,9,18,21). In this study, we addressed the causative role of NLV infections in cases of pediatric gastroenteritis and the molecular epidemiology of NLVs in Osaka City, Japan.…”
mentioning
confidence: 99%